Persepsi Orang Tua Tentang Pendidikan Seks Anak Usia Dini - Imam Azro’i; Atikah Triyani Simamora (Tinta Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This study is conducted to determine the perceptions of parents about early childhood sex education, to describe the factors that are predicted to influence parents' perceptions of early childhood sex education in Sri Mulyo Hamlet, Purwodadi Village, Tebing Tinggi District, Tanjung Jabung Barat Jambi Regency. This study used a qualitative descriptive method with a phenomenological study approach. The data collection techniques were obtained from observation, interviews, and documentation.The results of this study indicate that: first, parents have the perception that sex education for early childhood is important to teach, parents argue that by being taught sex education from an early age, children can maintain the privacy of their bodies, can get used to positive things from childhood, understand when in a state of danger or threat, and so that later when child is an adult, the child can understand the pros and cons of sex, so child can be careful in socializing. The two factors that are predicted to influence parents' perceptions of early childhood sex education are experiences obtained by parents, environmental factors in which parents live, economic factors of parents, and educational factors and parental knowledge about age child sex education early.